2014
DOI: 10.1111/scs.12147
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and health care consumption among older people

Abstract: Few studies have investigated loneliness in relation to health care consumption among frail older people. The aim of this study was to examine loneliness, health-related quality of life (HRQoL), and health complaints in relation to health care consumption of in- and outpatient care among frail older people living at home. The study, with a cross-sectional design, comprised a sample of 153 respondents aged from 65 years (mean age 81.5 years) or older, who lived at home and were frail. Data was collected utilisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
74
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 30 publications
15
74
3
Order By: Relevance
“…This association was observed in middle-aged and older but not younger individuals, which confirms results of previous studies [77–79]. Overall, lonely individuals might need to see a medical doctor more often because of their poor health.…”
Section: Discussionsupporting
confidence: 90%
“…This association was observed in middle-aged and older but not younger individuals, which confirms results of previous studies [77–79]. Overall, lonely individuals might need to see a medical doctor more often because of their poor health.…”
Section: Discussionsupporting
confidence: 90%
“…However, this group had the highest level of recent contact with medical services, a relationship also found in the Spanish study mentioned above [26]. Similarly, recent research has found that lonely older people have a higher use of health care services than nonlonely people [41] and that loneliness and social isolation are a common nonmedical problem presented by noncritically ill older people in emergency departments ([42], for a review, see [43]). One interpretation of this finding is that, in the absence of informal care and in the presence of need, older people will turn to medical services (perhaps primary care practitioners) in order to address their unmet need.…”
Section: Discussionsupporting
confidence: 55%
“…While not an experience unique to old age, loneliness is common among older adults, with 12% to 46% reporting at least some level of loneliness (Aartsen & Jylha, 2011; Dahlberg & McKee, 2014; Ellwardt, Aartsen, Deeg, & Steverink, 2013; Golden et al, 2009; Hawkley, Thisted, Masi, & Cacioppo, 2010; Holwerda et al, 2014; Lim & Kua, 2011; Netz, Goldsmith, Shimony, Arnon, & Zeev, 2013; Perissinotto, Cenzer, & Covinsky, 2012; Steptoe, Shankar, Demakakos, & Wardle, 2013; Victor & Bowling, 2012; van Beljouw et al, 2014). Loneliness among older adults is a concern of many countries around the world and has been documented in research studies in the United States (Hawkley et al, 2010; Perissinotto et al, 2012), the United Kingdom (Dahlberg & McKee, 2014; Steptoe et al, 2013), Ireland (McHugh & Lawlor, 2013; Schnittger, Wherton, Prendergast, & Lawlor, 2012), France (Amieva et al, 2010), Norway (Aanes, Hetland, Pallesen, & Mittelmark, 2011), the Netherlands (Ellwardt et al, 2013; van Beljouw et al, 2014), Finland (Aartsen & Jylha, 2011), Sweden (Taube, Kristensson, Sandberg, Midlov, & Jakobsson, 2014), Singapore (Lim & Kua, 2011), and Israel (Netz et al, 2013). Although estimates of loneliness vary due to differences in older populations studied as well as measures and definitions of loneliness used, prevalence rates for loneliness are remarkably consistent and stable over time across the scientific literature (Cacioppo, Hughes, Waite, Hawkley, & Thistel, 2006; Hawkley et al, 2010; Victor & Bowling, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics associated with loneliness generally include older age, widowhood/single status, lower income, poor health, functional limitations, hearing or vision impairments, depression, cognitive impairment, and loss of social networks/support (Aartsen & Jylha, 2011; Cacioppo et al, 2006; Cohen-Mansfield & Parpura-Gill, 2007; Dahlberg & McKee, 2014; Golden et al, 2009; Hawkley et al, 2010; Lim & Kua, 2011; Netz et al, 2013; Perissinotto et al, 2012; Pronk et al, 2011; Schnittger et al, 2012; Steptoe et al, 2013; Taube et al, 2014; van Beljouw et al, 2014; Victor & Bowling, 2012). Clinical outcomes associated with loneliness include depression, reduced sleep quality, increased blood pressure, physical inactivity, functional decline, cognitive impairment, and increased mortality (Aanes et al, 2011; Amieva et al, 2010; Buchman et al, 2010; Cacioppo et al, 2006; Cohen-Mansfield & Parpura-Gill, 2007; Dahlberg & McKee, 2014; Ellwardt et al, 2013; Hawkley et al, 2010; Holwerda et al, 2014; Lim & Kua, 2011; Luo et al, 2012; McHugh & Lawlor, 2013; Netz et al, 2013; Perissinotto et al, 2012; Steptoe et al, 2013; Taube et al, 2014; van Beljouw et al, 2014; Victor & Bowling, 2012).…”
Section: Introductionmentioning
confidence: 99%